Indústria 4.0 e mineração de processos como ferramenta estratégica para analisar o trâmite processual do sistema E-Proc no âmbito do Poder Judiciário do Tocantins - Oliveira, Júlio César Pereira de (Universidade Federal do Tocantins, 2022)
Process mining is a field of research related to data mining and business and process management. From this it is possible to analyze a large volume of data in a context and to identify patterns, models and behaviors, based on the logs. From mining, it is possible to propose improvements in institutional approaches and support the institution's strategic and decision-making process. This master's research work aimed to apply computational techniques of process mining with an evolutionary perspective with the use of artificial intelligence, in order to support the management of the judicial process within the scope of the Judiciary of Tocantins. It presents the use of statistics for the selection and classification of lawsuits and, finally, results about the volume of cases, points of congestion, equitable distribution of workforce and analysis of performance and compliance, considering a mapped procedural model. Finally, considering the performance of the Judiciary Power, it is guided through the National Council of Justice, it aligns with strategic objectives described in the various resolutions of this body and the resulting support in the use of process mining to achieve these objectives.